Elevated levels of circulating plasma sPDGFRβ in cognitively impaired APOE4 carriers - Abhay P. Sagare; Trevor Lohman; Ivan Ramirez; Elizabeth B. Joe; Michael G. Harrington; Helena C. Chui; Lon S. Schneider; Hussein N. Yassine; John M. Ringman; Arthur W. Toga; Daniel A. Nation; Berislav V. Zlokovic (GeroScience, 2026)
Increased levels of cerebrospinal fluid (CSF) soluble platelet-derived growth factor receptor-β (sPDGFRβ), a marker of blood–brain barrier (BBB)-associated pericyte cell injury, have been shown to correlate with increased BBB permeability and severity of Alzheimer’s disease (AD) pathology. It has been also shown that increased CSF sPDGFRβ levels can predict cognitive dysfunction in APOE4 carriers bearing the main susceptibility gene for AD. Whether plasma sPDGFRβ levels are also elevated in APOE4 carriers has not been explored. Here, we analyzed plasma samples for sPDGFRβ levels, Ab 42/40 ratio, and pTau217 in 115 APOE3 homozygotes and APOE4 carriers with Clinical Dementia Rating (CDR) score of 0 and 0.5. Our data show that plasma sPDGFRβ levels are increased in APOE4 carriers with cognitive impairment compared to APOE4 carriers that are cognitively unimpaired as well as relative to cognitively impaired APOE3 carriers even after controlling for plasma Aβ 42/40 ratio and pTau217. Thus, our data suggest that plasma sPDGFRβ is a useful biomarker of brain pericytes/BBB damage in APOE4 carriers.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

BDE-209-exposed melanoma cells enhance metastasis and chemoresistance in C57BL/6 mice - Micheli de Marchi; Erick Laurent Moggio; Mariliza Cristine Vieira da Costa; Izadora Volpato Rossi; Marcel Ivan Ramirez; Stellee Marcela Petris Biscaia; Francisco Filipak Neto; Ciro Alberto de Oliveira Ribeiro (Journal of Hazardous Materials, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Geographic perspectives on sustainability: Towards a conceptual framework - Miguel Angel Ramirez; Ivan Lizarazo (Environmental Development, 2025)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Phosphorus scarcity contributes to nitrogen limitation in lowland tropical rainforests - Helena Vallicrosa; Laynara F. Lugli; Lucia Fuchslueger; Jordi Sardans; Irene Ramirez‐Rojas; Erik Verbruggen; Oriol Grau; Laëtitia Bréchet; Guille Peguero; Leandro Van Langenhove; Lore T. Verryckt; César Terrer; et al. (Ecology, 2023)
There is increasing evidence to suggest that soil nutrient availability can limit the carbon sink capacity of forests, a particularly relevant issue considering today's changing climate. This question is especially important in the tropics, where most part of the Earth's plant biomass is stored. To assess whether tropical forest growth is limited by soil nutrients and to explore N and P limitations, we analyzed stem growth and foliar elemental composition of the five stem widest trees per plot at two sites in French Guiana after 3 years of nitrogen (N), phosphorus (P), and N + P addition. We also compared the results between potential N‐fixer and non‐N‐fixer species. We found a positive effect of N fertilization on stem growth and foliar N, as well as a positive effect of P fertilization on stem growth, foliar N, and foliar P. Potential N‐fixing species had greater stem growth, greater foliar N, and greater foliar P concentrations than non‐N‐fixers. In terms of growth, there was a negative interaction between N‐fixer status, N + P, and P fertilization, but no interaction with N fertilization. Because N‐fixing plants do not show to be completely N saturated, we do not anticipate N providing from N‐fixing plants would supply non‐N‐fixers. Although the soil‐age hypothesis only anticipates P limitation in highly weathered systems, our results for stem growth and foliar elemental composition indicate the existence of considerable N and P co‐limitation, which is alleviated in N‐fixing plants. The evidence suggests that certain mechanisms invest in N to obtain the scarce P through soil phosphatases, which potentially contributes to the N limitation detected by this study.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Detecting and tracking mesoscale precipitating objects using machine learning algorithms - Salomon Ramirez; Ivan Lizarazo (International Journal of Remote Sensing, 2017)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)

Comparison of Colombian and Costa Rican Strains of Rice Hoja Blanca Tenuivirus - Joachim R. De Miranda; Bertha-Cecilia Ramirez; Miguel Mun~oz; Ivan Lozano; Ray Wu; Anne-Lise Haenni; Ana M. Espinoza; Lee A. Calvert (Virus Genes, 1997)